Association of pharmaceutical care barriers and role ambiguity and role conflict of clinical pharmacists - Sun, Qingran; Wan, Chuchuan; Xu, Zhaoqi; Huang, Yuankai; Xi, Xiaoyu (Frontiers in Pharmacology, 2023)
Objectives. This study aimed to understand current status of pharmaceutical care barriers and explore the impact of them on the role ambiguity and role conflict of clinical pharmacists in secondary and tertiary hospitals in mainland China. Methods. The Chinese version of Role Conflict and Role Ambiguity Scale was used to measure clinical pharmacists’ role ambiguity and role conflict. A questionnaire for clinical pharmacists’ pharmaceutical care barriers was established to determine whether clinical pharmacists encounter barriers. Multiple linear regression model was used to analyze the influence of various pharmaceutical care barriers on the role ambiguity and role conflict of clinical pharmacists. Results. 1,300 clinical pharmacists from 31 provinces were eventually included. The results revealed that commonly perceived barriers to pharmaceutical care by clinical pharmacists include the lack of financial compensation and dedicated time for pharmaceutical care. Barriers such as clinical pharmacists’ unawareness of the importance of pharmaceutical care increase the degree of clinical pharmacists’ role conflict. And the lack of financial compensation for pharmaceutical care decreases the degree of role ambiguity, while barriers such as the lack of dedicated time for pharmaceutical care, the failure to standardize the service procedures and contents of related documents in health care institutions increase the degree of role ambiguity. Conclusion. Increased focus on enhancing financial compensation, responsibility cognition, education and training, and greater consideration of institutional factors could help clinical pharmacists better manage their work environments and provide higher-quality pharmaceutical care.